Preparation and evaluation of water-in-soybean oil–in-water emulsions by repeated premix membrane emulsification method using cellulose acetate membrane - Muhamad, I. I. (Springer India, 2016)
The purpose of this study was to investigate the preparation of formulated water– in–soybean oil–in–water emulsions by repeated premix membrane emulsification method using a cellulose acetate membrane. The effect of selective membrane emulsification process parameters (concentration of the emulsifiers, number of passes of the emulsions through the membrane and storage temperature) on the properties and stability of the developed emulsions were also investigated. 1, 3, 6, 8-pyrenetetrasulfonic acid tetrasodium salt (PTSA) was used as a hydrophilic model ingredient for the encapsulation of bioactive substances. W/O emulsions with 7 wt% (weight percentage) PGPR displays homogeneous and very fine dispersions, with the median diameter at 0.640 μm. Meanwhile, emulsions prepared by membrane emulsification (fine W/O/W) showed the highest stability at Tween 80 concentrations of 0.5 wt.% (weight percentage). It concluded that at 7 wt.% (weight percentage) PGPR concentration and 0.5 wt.% (weight percentage) Tween 80 concentrations, the most uniform particles with minimum mean size of oil drops (9.926 μm) were obtained after four passes through the membrane. Thus, cellulose acetate membrane can be used for preparing a stable W/O/W emulsions by repeated premix ME due to low cost and relatively easy to handle.